The best of enemies [videorecording (DVD)] - Bissell, Robin, 1968-; Henson, Taraji P; Rockwell, Sam; Heche, Anne; Davidson, Osha Gray (Universal Pictures Home Entertainment, 2019)
Racial tension runs high in 1971 Durham, North Carolina as residents continue to fight the 1954 Supreme Court decision to desegregate their schools. A series of town meetings are called to discuss the matter. Ann Atwater and C.P. Ellis, the meeting co-chairs, have very different views. Passionately advocating for school integration is a way of life for Atwater, a champion for Civil Rights. C.P. Ellis, Exalted Cyclops leading the Durham chapter of the Ku Klux Klan, vehemently opposes it. As the meetings progress, Atwater and Ellis learn they have more in common than they thought.